Estudo da restrição de geração eolioelétrica por constrained-off e aplicação da metodologia de obtenção de curva de produtividade eólica do operador nacional do sistema elétrico - Silva, Wendell Carlos Oliveira da (2022)
In some cases restrictions on the generation of electric energy are requested by the National Electric System Operator in order to maintain the criteria for the reliability of the National Interconnected Electricity System. The generation constraints that have originated externally to the installations of the electric power plants are known by the English term constrained-off. Such restrictions can be requested for any type of electric power generation plant being eolioelectric the focus of this work. Initially the concept of constrained-off and its treatment over the years by the National Electric Energy Agency is presented. Next the main points of normative resolution nº 927 of 2021 and the changes in submodule 2.4 of the network procedures regarding the prediction of generation constrained by constrained-off are listed. Using the calculation system proposed by the ONS this work presents a simplified methodology for the generating agent to obtain its productivity curve and thus follow the generation constraint imposed by the external agent. The methodology proposed here uses the Python programming language. The work also presents an analysis of the financial amount represented by the constrained-off generation constraints. Finally the work demonstrates that there is feasibility in the simplified methodology and the comparison between real generation and estimated generation through the obtained productivity curve proved to be satisfactory, with an approximate mean error of 8.15% and standard deviation of the error of 12.92% in the actual and estimated values.